Um estudo comparativo do violino na música popular brasileira: Fafá Lemos e Nicolas Krassik interpretam Fafá em Hollywood - Eliezer Anderson Batista Isidoro (2013)
This paper analyzes the technical and interpretative issues that involve the use of the violin in Brazilian popular music. The object of this study will be the piece Fafá in Hollywood, written by Fafá Lemos. Two different interpretations of the piece will be submitted to comparative analisys. The first one belongs to the album Fafá Lemos e seu violino com surdina (1955), played by Fafá Lemos. The second is part of the Nicolas Krassiks CD, Na Lapa (2004). We will analyze the technical and interpretative resources used by Lemos and Krassik in these recordings, investigating the presence of elements of Brazilian popular music and foreign music in these phonograms, both in terms of composition and interpretation. Subsequently, through this information we will discuss about the application of technical and interpretative elements of the violin in Brazilian popular music.